Helping behavior among preschool children at UP CDC - Tuazon, Rustico De Alday; Roldan, Aurorita T. (2000)
The study described the helping behaviors of school children in a school setting. It examined whether there was a significant difference between the types and motives of helping acts with preschool children's sex (male and female), age (younger and older) and grouping (homogeneous and heterogeneous). Forty-eight children (24 boys and 24 girls) were observed twice, 30 minutes each time during their work-play period. They were divided into four age groups. The researcher observed the different ways by which preschool children helped. The types of helping include sharing, giving, aiding, and comforting. Their motives of helping, that is, whether the helping act was performed through compliance, imitation, and self-initiation was noted using an observation form. Results revealed that there were no significant sex differences among male and female preschool children's helping behavior. Both boys and girls performed sharing, giving, aiding, and comforting types of helping. They performed helping acts through compliance, imitation, and self-initiation. No significant age differences were found between the types and motives of helping in younger and older children as well. However, there was a significant difference in the types of helping in grouping of children, particularly, sharing. Children in the heterogeneous grouping performed sharing more than children in a homogeneous grouping. There also was a significant difference with motive of compliance on the grouping of preschool children. Children in the heterogeneous grouping performed a high frequency of compliant helping acts than children in homogeneous group. No significant differences were found regarding imitation and self-initiation as motives of helping. Further studies of helping behavior with groupings of children as a variable is recommended. Helping behavior of children at home and outside the classroom could also be considered.
Thesis (M.F.L.C.D.)--University of the Philippines, Diliman.
Keywords: Helping behavior in children -- Philippines -- Diliman (Quezon City).